Light trapping in mesoporous solar cells with plasmonic nanostructures. Issue 5 (8th February 2016) - Erwin, William R.; Zarick, Holly F.; Talbert, Eric M.; Bardhan, Rizia
Abstract : This review article provides a comprehensive review of recent progress in plasmon-enhanced mesoporous solar cells and the mechanisms employed. Abstract : Plasmon resonances in metal nanostructures have been extensively harnessed for light trapping in mesoporous solar cells (MSCs), including dye-sensitized solar cells (DSSCs) and recently in perovskite solar cells (PSCs). By altering the geometry, dimension, and composition of metal nanostructures, their optical characteristics can be tuned to either overlap with the sensitizer absorption and enhance light harvesting, or absorb light at a wavelength complementary to the sensitizer enabling broadband solar light capture in MSCs. In this comprehensive review, we discuss the mechanisms of plasmonic enhancement in MSCs including far-field coupling of scattered light, near-field coupling of localized electromagnetic fields, hot electron transfer, and plasmon resonant energy transfer. We then summarize the progress in plasmon enhanced DSSCs in the past decade and decouple the impact of metal nanostructure shape, size, composition, and surface coatings on the overall efficiency. Further, we also discuss the recent advances in plasmon-enhanced perovskite solar cells. Distinct from other published reviews, we discuss the significance of femtosecond spectroscopies to probe the fundamental underpinnings of plasmon enhanced phenomena and understand the mechanisms that give rise to energy transfer between metal nanoparticles and solar materials. The review concludes with a discussion on the challenges in plasmonic device fabrication, and the promise of low-loss semiconductor nanocrystals for plasmonic enhancement in MSCs that facilitate light capture in the infrared.